Assessment of reporting quality in randomized controlled trials of acupuncture for labor pain - Jiang, Tao; Jiang, ShiYi; Cui, Ying; Yang, Ji-Peng; Du, Yuan-Hao; Li, Jing; Pang, Bo; Li, Bo (Frontiers in Pain Research, 2022)
Objective To evaluate the reporting quality of randomized controlled trials (RCTs) of acupuncture for labor pain, and to explore relevant factors for facilitating reporting transparency and integrity for future RCTs. Method Eight Chinese and English databases were systematically searched from their inception until August 31, 2021. General characteristics and methodological quality of the included reports were evaluated based on the CONSORT statement and the STRICTA guidelines. Descriptive statistical analysis was performed. Cohen's κ-statistics were calculated to assess the agreement of all items between two reviewers. Results A total of 84 RCTs were included. Based on the CONSORT statement, a positive reporting rate (greater than 80%) was evident for the items “trial design” “participants” “intervention” “outcomes” “numbers analyzed” and “generalizability”. The quality of reporting for the items “randomized in the title or abstract” “sample size” “allocation concealment” “implementation” “blinding” “recruitment” “ancillary analyses” “harms” “interpretation” “registration” and “protocol” was poor with positive rates less than 10%. Based on the STRICTA guidelines, the items “extent to which treatment varied” “number of needle insertions per subject per session” and “control or comparator interventions” had poor reporting quality with positive rates of less than 10%. Substantial agreement was observed for most items and excellent agreement for some items. Conclusion The reporting quality of RCTs of acupuncture for labor pain is suboptimal generally. Rigorous adherence to the CONSORT statement and the STRICTA guidelines should be emphasized in future studies to improve the quality of acupuncture RCT reports.